IEEE 10th International Conference on Industrial Informatics 2012
DOI: 10.1109/indin.2012.6301139
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for service robots operating in non-industrial environments

Abstract: The concept of service robotics has grown considerably over the past two decades with many robots being used in non-industrial environments such homes, hospitals and airports. Many of these environments were never designed to have mobile service robots deployed within them. This paper describes some of the challenges that are faced and need to be overcome in order for robots to successfully work in nonindustrial environments (specifically homes and hospitals). These include the problems caused by an environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Kawamura et al puts forward a design philosophy for service robots that emphasizes compromise and practicality in design [15]. Although Soroka et al have identified some of these challenges [16], systemic design principles that aim for seamless integration of service robots and humans in everyday environments still have yet to be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Kawamura et al puts forward a design philosophy for service robots that emphasizes compromise and practicality in design [15]. Although Soroka et al have identified some of these challenges [16], systemic design principles that aim for seamless integration of service robots and humans in everyday environments still have yet to be discussed.…”
Section: Introductionmentioning
confidence: 99%